SiNiSan Ameliorates the Depression-Like Behavior of Rats That Experienced Maternal Separation Through 5-HT1A Receptor/CREB/BDNF Pathway - Cao, Kerun; Shen, Chongkun; Yuan, Yumei; Bai, Shasha; Yang, Lei; Guo, Lili; Zhang, Rong; Shi, Yafei (Frontiers in Psychiatry, 2019)
Background: Early adverse life stress is an important dangerous factor to develop kinds of psychiatric disorders, particularly depression. In current, clinical antidepressant agents such as fluoxetine, a selective serotonin reuptake inhibitors (SSRIs), are unsatisfactory because of the side effects. SiNiSan (SNS) is the classic Chinese medicine prescription regarded as dispersing stagnated liver qi for relieving qi stagnation. Therefore, this study was designed to detect the effects and molecular mechanism of SNS treatment in rats subjected maternal separation(MS). Method: Male neonatal Wistar rats were divided into 6 groups including control + ddH2O, MS + ddH2O, MS + fluoxetine (0.5mg/mL), MS + SNS low dose(0.25g/mL), MS + SNS medium dose(0.5g/mL), MS + SNS high dose(1g/mL),16 pup/group, 8 pups for young, 8 pups for adult. Except control group, all pups of MS groups had been separated from mothers for 4 hours per day from 9:00-13:00 during PND (postnatal day) 1 to 21. After MS, the 6 groups were administrated respectively ddH2O, fluoxetine, and different dose of SNS intragastrically (ig.) until PND28 (for young) and PND56 (for adult). Weigh every day, and depression-like behaviors were assessed by sucrose preference test, open field test (OFT) and forced swimming test. serotonin 1A (5-HT1A) receptor, phosphorylated protein kinase A (p-PKA) substrate, cAMP response element-binding protein (CREB), p-CREB and brain-derived neurotrophic factor (BDNF) in hippocampus were examined by WB, in situ 5-HT1A receptor expression were measure by IHC. Results: The MS rats performed the depression-like behaviors in youth and adult. However, the depression-like behaviors were ameliorated by SNS both in young and adult rats. The level of 5-HT1A receptor, p-CREB and BDNF in hippocampus were reduced in young and adult MS rats. SNS treatment significantly up-regulated the expression of 5-HT1A receptor, p-CREB and BDNF in hippocampus of adult MS rats, but few significant effects on the protein expression was observed in young. Conclusion: Maternal separation in infancy could develop depression-like behaviors in young and adult. SNS treatment may perform the antidepressant effects on both young and adult MS rats through the BDNF/PKA/CREB pathway.